1998
DOI: 10.1002/(sici)1521-4109(199806)10:7<472::aid-elan472>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Use of Prussian Blue/Conducting Polymer Modified Electrodes for the Detection of Cytochrome C

Abstract: In this work, the development and utilization of a Prussian blue/conducting polymer composite electrode has been investigated. The introduction of a layer of conducting polymer (polypyrrole) enhanced the electroactivity of the outer Prussian blue film. This has been used for improved signal generation for the redox protein cytochrome c. The effect of the thickness of these two film coatings and buffer solution pH has been investigated. The analytical utility has been demonstrated using flow injection analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…It was found that PB films have been deposited on glassy carbon [29][30][31][35][36][37][38][39], graphite [30,32,33,39], platinum [40,41] and carbon fiber [28] and also incorporated into polypyrrole [42,43] and carbon paste [44][45][46]. Our group first announced the development of transition metal ferricyanide modified electrodes on the basis of Al substrate [47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that PB films have been deposited on glassy carbon [29][30][31][35][36][37][38][39], graphite [30,32,33,39], platinum [40,41] and carbon fiber [28] and also incorporated into polypyrrole [42,43] and carbon paste [44][45][46]. Our group first announced the development of transition metal ferricyanide modified electrodes on the basis of Al substrate [47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, much effort has been focused on the preparation of noble metal (such as Au and Ag) and conducting polymer composites because of their superior performance as nanocircuits, nanodevices, and nanosensors [26,27]. Although PPy/PB composite films [19,28,29] and PPy/Ag composites [30][31][32] are well documented, the composite nanotubes are rarely reported. Pyrrole monomer can be oxidized by potassium ferricyanide (KHCF) [33] or silver nitrate to form PPy and, PB or Ag [31,32], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the search for suitable matrices for PB immobilization, it is found that PB films have been deposited on a variety of surfaces, the most being glassy carbon [12,[15][16][17]19,23,24,31,32], graphite [18,20,21,33], platinum [34,35] and carbon fiber [22]. It has been also incorporated into polypyrroles [36,37] and very little attention has been given to carbon paste electrodes modified with PB [14,[38][39][40].…”
Section: Introductionmentioning
confidence: 99%